Transition metal modified MoS2 catalyst, preparation method and application of transition metal modified MoS2 catalyst in electrochemical reduction of N2O to synthesize ammonia
By reducing N2O to ammonia under electrochemical conditions through transition metal modified MoS2 catalyst, the problem of low N2O reduction ammonia in the prior art was solved, and efficient and environmentally friendly ammonia synthesis was achieved, becoming the cleaning of the Haber-Boss process Alternative.
Patent Information
- Application Number
- CN202411367881.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-29
- Publication Date
- 2024-12-17
AI Technical Summary
The existing electrochemical reduction of N2 ammonia synthesis technology has low activity and Faraday efficiency, and lacks research on N2O, which is a source of greenhouse gases and ozone layer hollows, and has severe environmental pollution.
Using transition metal modified MoS2 catalysts, efficient catalysts are prepared through hydrothermal synthesis and protection gas treatment, and reducing N2O to ammonia under electrochemical conditions, providing a new electrochemical synthesis pathway.
Improves catalytic performance, achieves sustainable, flexible and efficient ammonia synthesis, and becomes a clean alternative to the Haber-Boss process, reducing carbon emissions and improving the active site exposure of the catalyst.
Smart Images

Figure CN119144987A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of electrochemical catalysts, and in particular to a transition metal modified MoS2 catalyst and a preparation method thereof, and application thereof in electrochemical reduction of N2O to synthesize ammonia. Background Art
[0002] Ammonia is one of the most important basic chemical raw materials in people's daily production and life. It is mainly used in the production of nitrogen fertilizer in agriculture. In addition, it also has good application prospects in the energy field and can be used as a hydrogen carrier material. In recent years, the direct electrochemical reduction of oxidized nitrogen to ammonia driven by electricity generated by renewable energy has been proposed as a clean and sustainable alternative to the Haber-Bosch process.
[0003] At present, electrochemical reduction of N2 to synthesize ammonia has been widely studied, but improving its activity and Faraday efficiency (FE) remains a huge challenge. In a typical N2 ammonia synthesis system, nitrogen molecules are adsorbed by the binding force between the catalytic active sites on the heterogeneous surface of the electrocatalyst and non-polar nitrogen, and are oxidized through a complex five-electron oxidation process using water molecules as solvent and oxygen source. In this process, due to poor optimization of the catalyst structure, the binding force is always too weak to break the strong N≡N triple bond, resulting in unsatisfactory nitrogen oxidation rate and Faraday efficiency. At the same time, the hydrogen evolution reaction (HER) associated with the electrochemical reduction of nitrogen oxides to synthesize ammonia is a competitive reaction, and the synthesis of NH3 is more difficult.
[0004] Therefore, the scientific community seeks other electrochemical pathways to produce ammonia, for example, from oxidized forms of nitrogen such as nitrates, NO, and NO2. However, despite some challenging attempts in recent years, there are still some practical limitations. N2O is the third largest greenhouse gas with an extremely high greenhouse effect value. It is also the source of nitrogen oxides in the stratosphere, which can cause ozone holes and harm the environment, becoming one of the gases that seriously pollute the environment. In the field of electrochemical reduction of oxidized nitrogen to ammonia, there is currently a lack of research on N2O, so research on electrochemical reduction of N2O to synthesize ammonia is very necessary.
[0005] CN117985761A discloses an iron-fluorine dual-doped tungsten disulfide nanocatalyst and its preparation method and use. First, the iron-doped tungsten disulfide precursor is uniformly grown on the substrate material by hydrothermal method, and then fluorine doping is introduced by low-temperature fluorination to obtain an iron-fluorine dual-doped tungsten disulfide nanocatalyst. At -0.25V, the iron-fluorine dual-doped tungsten disulfide nanocatalyst (Fe, F-WS2) has the best activity and a Faraday efficiency of 22.42%. However, the preparation method requires Fe, F bimetallic doping, the preparation process is complicated, and it is only applicable to electrocatalytic reduction of N2 to synthesize ammonia.
[0006] CN118048646A discloses a preparation method, product and application of a phosphomolybdic acid-regulated metal organic framework Cu-MOF catalyst, wherein copper nitrate, phosphomolybdic acid and 1,3,5-benzenetricarboxylic acid are first added to a solvent consisting of anhydrous ethanol and deionized water, and a mixed solution is obtained after ultrasonic treatment; the mixed solution is transferred to a polytetrafluoroethylene-lined autoclave for heating and reaction; after the reaction is completed, the autoclave is taken out and centrifuged, washed and dried to obtain a catalyst. However, the preparation method requires the use of a phosphomolybdic acid oxidant, which may aggravate combustion and is relatively dangerous. Summary of the invention
[0007] In view of the problems and shortcomings of the prior art, the present invention provides a transition metal modified MoS2 catalyst and a preparation method thereof and its application in electrochemical reduction of N2O to synthesize ammonia.
[0008] In order to achieve the above-mentioned purpose of the present invention, the following technical solutions are particularly adopted:
[0009] The first aspect of the present invention provides a method for preparing a transition metal modified MoS2 catalyst, comprising the following steps:
[0010] (1) dissolving molybdate and a sulfur-containing organic compound in water, stirring at room temperature for 30 to 45 minutes, and then performing a hydrothermal synthesis reaction at 160 to 200° C. for 20 to 28 hours, washing the hydrothermal synthesis product with water and ethanol, and then drying to obtain MoS2;
[0011] (2) dissolving the transition metal salt and the MoS2 prepared in step (1) in an ethanol aqueous solution, stirring the reaction at room temperature for 4 to 6 hours, washing with water by centrifugation until neutral, and then drying to obtain a transition metal-doped MoS2 catalyst;
[0012] (3) The transition metal-doped MoS2 catalyst prepared in step (2) is maintained at a temperature of 200 to 400°C at a heating rate of 1°C / min under a protective gas atmosphere for 2 to 4 hours, and then naturally cooled to room temperature to obtain a transition metal-modified MoS2 catalyst.
[0013] Preferably, the molar ratio of the molybdate to the sulfur-containing organic compound in step (1) is 1:(30-50);
[0014] The molybdate is (NH4)6Mo7O 24 , at least one of Na2MoO4;
[0015] The sulfur-containing organic compound is at least one of C2H5NS and CH4N2S.
[0016] Furthermore, the hydrothermal synthesis reaction in step (1) is carried out in a reactor, which is a stainless steel reactor lined with polytetrafluoroethylene.
[0017] Preferably, in step (2), the molar ratio of the transition metal salt to MoS2 is (0.5-2):1; and the volume fraction of the ethanol aqueous solution is 25%.
[0018] More preferably, the transition metal in step (2) is at least one of Cu, Ni, Mn and Co; and the transition metal salt is at least one of acetate, nitrate and sulfate of the corresponding metal.
[0019] Preferably, the protective gas in step (3) is He, N2 or Ar.
[0020] More preferably, in step (3), the transition metal-doped MoS2 catalyst powder is spread flat on a magnetic boat, and then placed in a tubular furnace and heated under a protective gas atmosphere.
[0021] The second aspect of the present invention provides a transition metal modified MoS2 catalyst prepared by any step of the preparation method described in the first aspect above.
[0022] The third aspect of the present invention provides the use of the transition metal modified MoS2 catalyst described in the second aspect in the electrochemical reduction of N2O to synthesize ammonia.
[0023] A fourth aspect of the present invention provides a method for synthesizing ammonia by electrochemical reduction of N2O, comprising the following steps:
[0024] The transition metal modified MoS2 catalyst was evenly dispersed after ultrasonic treatment and then dropped on carbon paper to make a working electrode, which was then assembled into a three-electrode system; in the three-electrode system, 0.1 mol / L Na2SO4 solution was used as the electrolyte, Ag / AgCl was used as the reference electrode, and the glassy carbon electrode was used as the counter electrode; the three-electrode system was connected to an electrochemical workstation, and ammonia was synthesized by catalytic reaction for 1 to 5 hours at a voltage range of 0 to 1.8 V in an N2O atmosphere of 5 to 10 mL / min.
[0025] Preferably, the uniform dispersion of the transition metal-modified MoS2 catalyst is carried out with the aid of the solvents ethanol and naphthol.
[0026] Preferably, the volume of the electrolyte is 30-40 mL.
[0027] Beneficial effects of the present invention:
[0028] 1. Existing research on electrochemical synthesis of ammonia generally involves electrocatalysis of nitrate, NO, NO2 and N2. The present invention provides a new electrochemical synthesis of ammonia, which synthesizes ammonia from N2O through electrochemical reduction.
[0029] 2. The present invention uses transition metal-modified MoS2 as a catalyst to electrochemically reduce N2O to synthesize ammonia. After the transition metal is modified, the transition metal is doped in the MoS2 lattice, which makes the catalytic performance good. The N cycle electrocatalysis is sustainable, flexible and compatible, and converts renewable energy into value-added chemicals with minimal carbon emissions, becoming one of the clean and sustainable alternatives to the Haber-Bosch process.
[0030] 3. When preparing transition metal-modified MoS2, the present invention uses He, N2 or Ar as a protective gas to further treat M-MoS2 (M is a metal ion), and the catalytic performance of the catalyst is significantly improved. This is because the number of layers of the multilayer structure of molybdenum disulfide is reduced, thereby exposing more active sites. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Figure 1 Reaction diagram for the electrochemical reduction of N2O to NH3.
[0032] Figure 2 The linear sweep voltammetry curve of the working electrode made of the catalyst of Example 1 under Ar and N2O atmosphere;
[0033] Among them, (a) is Cu-MoS2-1.0, and (b) is Cu-MoS2-1.0-Ar.
[0034] Figure 3 The linear sweep voltammetry curve of the working electrode made of the catalyst of Example 2 under Ar and N2O atmosphere;
[0035] Among them, (a) is Cu-MoS2-0.5, and (b) is Cu-MoS2-0.5-Ar.
[0036] Figure 4 The linear sweep voltammetry curve of the working electrode made of the catalyst of Example 3 under Ar and N2O atmosphere;
[0037] Among them, (a) is Cu-MoS2-2.0, and (b) is Cu-MoS2-2.0-Ar.
[0038] Figure 5 The linear sweep voltammetry curve of the working electrode made of the catalyst of Example 4 under Ar and N2O atmosphere;
[0039] Among them, (a) is Ni-MoS2-1.0, and (b) is Ni-MoS2-1.0-Ar.
[0040] Figure 6 The linear sweep voltammetry curve of the working electrode made of the catalyst of Example 5 under Ar and N2O atmosphere;
[0041] Among them, (a) is Ni-MoS2-0.5, and (b) is Ni-MoS2-0.5-Ar.
[0042] Figure 7 The linear sweep voltammetry curve of the working electrode made of the catalyst of Example 6 under Ar and N2O atmosphere;
[0043] Among them, (a) is Ni-MoS2-2.0, and (b) is Ni-MoS2-2.0-Ar.
[0044] Figure 8 The linear sweep voltammetry curve of the working electrode made of the catalyst of Example 7 under Ar and N2O atmosphere;
[0045] Among them, (a) is Co-MoS2-1.0, and (b) is Co-MoS2-1.0-Ar.
[0046] Fig. 9 The linear sweep voltammetry curve of the working electrode made of the catalyst of Example 8 under Ar and N2O atmosphere;
[0047] Among them, (a) is Co-MoS2-0.5, and (b) is Co-MoS2-0.5-Ar.
[0048] Fig.10 The linear sweep voltammetry curve of the working electrode made of the catalyst of Example 9 under Ar and N2O atmospheres;
[0049] Among them, (a) is Co-MoS2-2.0, and (b) is Co-MoS2-2.0-Ar.
[0050] Fig.11 The linear sweep voltammetry curve of the working electrode made of the catalyst of Example 10 under Ar and N2O atmospheres;
[0051] Among them, (a) is Mn-MoS2-0.5, and (b) is Mn-MoS2-0.5-Ar.
[0052] Fig.12 The linear sweep voltammetry curve of the working electrode made of the catalyst of Example 11 under Ar and N2O atmospheres;
[0053] Among them, (a) is Mn-MoS2-2.0, and (b) is Mn-MoS2-2.0-Ar.
[0054] Fig.13 This is a characterization test diagram of the catalyst of Example 7;
[0055] Among them, (a) is the XRD spectrum, (b) is the Raman spectrum, and (c) is the XPS spectrum.
[0056] Fig.14 The linear sweep voltammetry curve of the working electrode made of the catalyst of Comparative Example 1 under Ar and N2O atmospheres;
[0057] Among them, (a) is MoS2 and (b) is MoS2-Ar. DETAILED DESCRIPTION
[0058] Example 1-3 Preparation and Application of Metallic Copper Modified MoS2
[0059] Example 1
[0060] A method for preparing a transition metal modified MoS2 catalyst for electrochemical reduction of N2O to synthesize ammonia comprises the following steps:
[0061] (1) 1.2 g of ammonium molybdate tetrahydrate ((NH4)6Mo7O 24 ·4H2O) and 2.3g thiourea (CH4N2S) were dissolved in 40mL deionized water and stirred at room temperature for 30min. The stirred reaction solution was transferred to a 50mL polytetrafluoroethylene-lined stainless steel reactor and placed in an oven for hydrothermal synthesis. The reaction temperature was 160°C and the reaction time was 28h. The product obtained by hydrothermal synthesis was washed with deionized water and ethanol, then dried in an oven at 60°C for 4h, and ground to obtain MoS2 powder;
[0062] (2) According to the molar ratio of copper acetate tetrahydrate to MoS2 of 1:1, 1.99 g of copper acetate tetrahydrate Cu(CH3COO)2·H2O and 1.6 g of MoS2 powder prepared in step (1) were dissolved in 400 mL of 25% ethanol aqueous solution, stirred and reacted at room temperature for 6 h, the obtained product was centrifuged with deionized water to neutrality, and then placed in a vacuum oven at 100°C and dried for 6 h to obtain a Cu-MoS2-1.0 catalyst;
[0063] (3) The Cu-MoS2-1.0 catalyst prepared in step (2) was ground into powder and spread on a magnetic boat, then placed in a tubular furnace, maintained at 200°C for 2 h at a heating rate of 1°C / min under an Ar atmosphere, and then naturally cooled to room temperature to obtain a Cu-MoS2-1.0-Ar catalyst.
[0064] The method for synthesizing ammonia by electrochemical reduction of N2O using the above catalyst is shown in Figure 1 , including the following steps:
[0065] 5 mg of Cu-MoS2-1.0 or Cu-MoS2-1.0-Ar catalyst was evenly dispersed after ultrasonic treatment and then dropped on carbon paper to make a working electrode, which was then assembled into a three-electrode system; in the three-electrode system, 40 mL of 0.1 mol / L Na2SO4 solution was used as the electrolyte, Ag / AgCl was used as the reference electrode, and the glassy carbon electrode was used as the counter electrode; the three-electrode system was connected to an electrochemical workstation and worked for 1 h in a 10 mL / min N2O atmosphere to synthesize ammonia, with a working voltage of -1.1 V (vs. ref).
[0066] Example 2
[0067] A method for preparing a transition metal-modified MoS2 catalyst for electrochemical reduction of N2O to synthesize ammonia, wherein the steps are substantially the same as those of Example 1, except that: in step (2), the molar ratio of copper acetate tetrahydrate to MoS2 is 0.5:1; a Cu-MoS2-0.5 catalyst and a Cu-MoS2-0.5-Ar catalyst are prepared respectively, and the corresponding catalysts are used to electrochemically reduce N2O to synthesize ammonia.
[0068] Example 3
[0069] A method for preparing a transition metal modified MoS2 catalyst for electrochemical reduction of N2O to synthesize ammonia, wherein the steps are substantially the same as those of Example 1, except that the molar ratio of copper acetate tetrahydrate to MoS2 in step (2) is 2:1. A Cu-MoS2-2.0 catalyst and a Cu-MoS2-2.0-Ar catalyst are prepared respectively, and the corresponding catalysts are used to electrochemically reduce N2O to synthesize ammonia.
[0070] After the reaction, 2 mL of electrolyte was taken and the appearance potential value and ammonia concentration of the product ammonia in Examples 1 to 3 were tested by the indophenol blue detection method. The results are shown in Table 1. Under 10 mL / min Ar and N2O atmosphere, the linear sweep voltammetric curves (LSV curves) of the working electrodes made of Cu-MoS2 and Cu-MoS2-Ar catalysts at various molar ratios were measured. The test voltage range was -1.8 to -0.7 V (vs. ref). The results are shown in Table 1. Figures 2 to 4 shown.
[0071] Table 1 Ammonia concentrations of Cu-MoS2 and Cu-MoS2-Ar electrocatalyzed N2O synthesis at different molar ratios of copper acetate tetrahydrate and MoS2
[0072] Material Potential V (vs.ref) Ammonia concentration (ppm) <![CDATA[Cu-MoS2-0.5]]> -1.261 0.079 <![CDATA[Cu-MoS2-1.0]]> -1.1 0.113 <![CDATA[Cu-MoS2-2.0]]> -1.261 0.076 <![CDATA[Cu-MoS2-0.5-Ar]]> -1.211 0.152 <![CDATA[Cu-MoS2-1.0-Ar]]> -1.1 0.253 <![CDATA[Cu-MoS2-2.0-Ar]]> -1.211 0.144
[0073] As can be seen from Table 1, when Cu-MoS2-Ar, obtained by treating Cu-MoS2 with Ar, is used as a catalyst to synthesize ammonia, the ammonia concentration is greater than the concentration of ammonia synthesized by Cu-MoS2, which indicates that the performance of the catalyst in synthesizing ammonia has been improved after being treated with protective gas. When the molar ratio of copper acetate tetrahydrate to MoS2 is 1:1, the ammonia concentration is the highest and the effect of catalytic synthesis of ammonia is the best. Figures 2 to 4 From the comparison between Figure (a) and Figure (b), it can be seen that at different molar ratios of copper acetate tetrahydrate and MoS2, the current density of the working electrode made of Cu-MoS2 and Cu-MoS2-Ar catalysts in N2O atmosphere is greater than that in Ar gas atmosphere, and the presence of product NH3 can be seen from Table 1, indicating that N2O can be reduced to ammonia by electrochemical means.
[0074] Examples 4 to 6 Preparation and Application of Metal Nickel-Modified MoS2
[0075] Example 4
[0076] A method for preparing a transition metal modified MoS2 catalyst for electrochemical reduction of N2O to synthesize ammonia comprises the following steps:
[0077] (1) 1.2 g of ammonium molybdate tetrahydrate ((NH4)6Mo7O 24 ·4H2O) and 2.3g thiourea (CH4N2S) were dissolved in 40mL deionized water and stirred at room temperature for 45min. The stirred reaction solution was transferred to a 50mL stainless steel reactor lined with polytetrafluoroethylene and placed in an oven for hydrothermal reaction synthesis. The reaction temperature was 180°C and the reaction time was 24h. The product obtained by hydrothermal synthesis was washed with deionized water and ethanol, then dried in an oven at 70°C for 3h, and ground to obtain MoS2 powder;
[0078] (2) According to the molar ratio of nickel acetate tetrahydrate to MoS2 of 1:1, 2.5 g of nickel acetate tetrahydrate Ni(CH3COO)2·4H2O and 1.6 g of MoS2 powder prepared in step (1) were dissolved in 400 mL of 25% ethanol aqueous solution, stirred and reacted at room temperature for 5 h, the obtained product was centrifuged with deionized water to neutrality, and then placed in a vacuum oven at 80°C for 4 h to obtain a Ni-MoS2-1.0 catalyst;
[0079] (3) The Ni-MoS2-1.0 catalyst prepared in step (2) was ground into powder and spread on a magnetic boat, then placed in a tubular furnace, maintained at 350°C for 3 h at a heating rate of 1°C / min under an Ar atmosphere, and then naturally cooled to room temperature to obtain a Ni-MoS2-1.0-Ar catalyst.
[0080] The method for synthesizing ammonia by electrochemical reduction of N2O using the above catalyst comprises the following steps:
[0081] 5 mg of Ni-MoS2-1.0 or Ni-MoS2-1.0-Ar catalyst was evenly dispersed after ultrasonic treatment and then dropped on carbon paper to make a working electrode, which was then assembled into a three-electrode system; in the three-electrode system, 40 mL of 0.1 mol / L Na2SO4 solution was used as the electrolyte, Ag / AgCl was used as the reference electrode, and the glassy carbon electrode was used as the counter electrode; the three-electrode system was connected to an electrochemical workstation and worked for 1 h in a 10 mL / min N2O atmosphere to synthesize ammonia, with a working voltage of -0.7 V (vs. ref).
[0082] Example 5
[0083] A method for preparing a transition metal-modified MoS2 catalyst for electrochemical reduction of N2O to synthesize ammonia, wherein the steps are substantially the same as those of Example 4, except that: in step (2), the molar ratio of nickel acetate tetrahydrate to MoS2 is 0.5:1; Ni-MoS2-0.5 catalyst and Ni-MoS2-0.5-Ar catalyst are prepared respectively, and the corresponding catalysts are used to electrochemically reduce N2O to synthesize ammonia.
[0084] Example 6
[0085] A method for preparing a transition metal-modified MoS2 catalyst for electrochemical reduction of N2O to synthesize ammonia, wherein the steps are substantially the same as those of Example 4, except that: in step (2), the molar ratio of nickel acetate tetrahydrate to MoS2 is 2:1; Ni-MoS2-2.0 catalyst and Ni-MoS2-2.0-Ar catalyst are prepared respectively, and the corresponding catalysts are used to electrochemically reduce N2O to synthesize ammonia.
[0086] After the reaction, 2 mL of electrolyte was taken and the appearance potential value and ammonia concentration of the product ammonia in Examples 4 to 6 were tested by the indophenol blue detection method. The results are shown in Table 2. Under 10 mL / min Ar and N2O atmosphere, the linear sweep voltammetric curves (LSV curves) of the working electrodes made of Ni-MoS2 and Ni-MoS2-Ar catalysts at various molar ratios were measured. The test voltage range was -1.8 to -0.7 V (vs. ref). The results are shown in Table 2. Figures 5 to 7 shown.
[0087] Table 2 Ammonia concentrations of Ni-MoS2 and Ni-MoS2-Ar electrocatalyzed N2O synthesis at different molar ratios of nickel acetate tetrahydrate and MoS2
[0088] Material Potential V (vs.ref) Ammonia concentration (ppm) <![CDATA[Ni-MoS2-0.5]]> -0.911 0.069 <![CDATA[Ni-MoS2-1.0]]> -0.7 0.124 <![CDATA[Ni-MoS2-2.0]]> -0.911 0.077 <![CDATA[Ni-MoS2-0.5-Ar]]> -0.711 0.231 <![CDATA[Ni-MoS2-1.0-Ar]]> -0.7 0.277 <![CDATA[Ni-MoS2-2.0-Ar]]> -0.711 0.186
[0089] As can be seen from Table 2, when Ni-MoS2-Ar, obtained by treating Ni-MoS2 with Ar, is used as a catalyst for catalytic synthesis of ammonia, the ammonia concentration is greater than the concentration of ammonia synthesized by Ni-MoS2, which indicates that the performance of the catalyst for catalytic synthesis of ammonia has been improved after being treated with protective gas. When the molar ratio of nickel acetate tetrahydrate to MoS2 is 1:1, the ammonia concentration is the highest and the catalytic synthesis of ammonia is the best. Figures 5 to 7 Comparison between Figure (a) and Figure (b) shows that, at different molar ratios of nickel acetate tetrahydrate and MoS2, the current density of the working electrode made of Ni-MoS2 and Ni-MoS2-Ar catalysts in N2O atmosphere is greater than that in Ar gas atmosphere, and the presence of product NH3 can be seen from Table 2, indicating that N2O can be reduced to synthesize ammonia by electrochemical means. Examples 7-9 Preparation and application of metal cobalt modified MoS2
[0090] Example 7
[0091] A method for preparing a transition metal modified MoS2 catalyst for electrochemical reduction of N2O to synthesize ammonia comprises the following steps:
[0092] (1) 1.2 g of ammonium molybdate tetrahydrate ((NH4)6Mo7O 24 ·4H2O) and 2.3g thiourea (CH4N2S) were dissolved in 40mL deionized water and stirred at room temperature for 35min. The stirred reaction solution was transferred to a 50mL polytetrafluoroethylene-lined stainless steel reactor and placed in an oven for hydrothermal synthesis. The reaction temperature was 190℃ and the reaction time was 25h. The product obtained by hydrothermal synthesis was washed with deionized water and ethanol, then dried in an oven at 75℃ for 2h and ground to obtain MoS2 powder.
[0093] (2) According to the molar ratio of cobalt acetate tetrahydrate to MoS2 of 1:1, 2.5 g of cobalt acetate tetrahydrate Co(CH3COO)2·4H2O and 1.6 g of MoS2 powder prepared in step (1) were dissolved in 400 mL of 25% ethanol aqueous solution, stirred and reacted at room temperature for 6 h, the obtained reaction solution was centrifuged with deionized water to neutrality, and then placed in a vacuum oven at 95°C for 6 h to obtain a Co-MoS2-1.0 catalyst;
[0094] (3) The Co-MoS2-1.0 catalyst prepared in step (2) was ground into powder and spread on a magnetic boat, then placed in a tubular furnace, maintained at 400°C for 2 h at a heating rate of 1°C / min under an Ar atmosphere, and then naturally cooled to room temperature to obtain a Co-MoS2-1.0-Ar catalyst.
[0095] The method for synthesizing ammonia by electrochemical reduction of N2O using the above catalyst comprises the following steps:
[0096] 5 mg of Co-MoS2-1.0 or Co-MoS2-1.0-Ar catalyst was uniformly dispersed and dropped on carbon paper to make a working electrode, and then assembled into a three-electrode system; in the three-electrode system, 40 mL of 0.1 mol / L Na2SO4 solution was used as the electrolyte, Ag / AgCl was used as the reference electrode, and the glassy carbon electrode was used as the counter electrode; the three-electrode system was connected to an electrochemical workstation and worked for 1 h in a 10 mL / min N2O atmosphere to synthesize ammonia, and the working voltage was -0.9 V (vs.ref).
[0097] Example 8
[0098] A method for preparing a transition metal-modified MoS2 catalyst for electrochemical reduction of N2O to synthesize ammonia, wherein the steps are substantially the same as those of Example 7, except that: in step (2), the molar ratio of cobalt acetate tetrahydrate to MoS2 is 0.5:1; Co-MoS2-0.5 catalyst and Co-MoS2-0.5-Ar catalyst are prepared respectively, and the corresponding catalysts are used for electrochemical reduction of N2O to synthesize ammonia.
[0099] Example 9
[0100] A method for preparing a transition metal-modified MoS2 catalyst for electrochemical reduction of N2O to synthesize ammonia, wherein the steps are substantially the same as those of Example 7, except that: in step (2), the molar ratio of cobalt acetate tetrahydrate to MoS2 is 0.5:1; Co-MoS2-2.0 catalyst and Co-MoS2-2.0-Ar catalyst are prepared respectively, and the corresponding catalysts are used for electrochemical reduction of N2O to synthesize ammonia.
[0101] After the reaction, 2 mL of electrolyte was taken and the appearance potential and ammonia concentration of the product ammonia in Examples 7 to 9 were detected with indophenol blue. The results are shown in Table 3. In an Ar and N2O atmosphere at 10 mL / min, the LSV curves of the working electrodes made of Co-MoS2 and Co-MoS2-Ar catalysts at various molar ratios were measured. The test voltage range was -1.8 to -0.7 V (vs. ref). The results are shown in Table 3. Figures 8 to 10 shown.
[0102] Table 3 Ammonia concentrations of Co-MoS2 and Co-MoS2-Ar electrocatalyzed N2O synthesis at different molar ratios of cobalt acetate tetrahydrate and MoS2
[0103] Material Potential V (vs.ref) Ammonia concentration (ppm) <![CDATA[Co-MoS2-0.5]]> -1.011 0.082 <![CDATA[Co-MoS2-1.0]]> -0.9 0.101 <![CDATA[Co-MoS2-2.0]]> -1.011 0.088 <![CDATA[Co-MoS2-0.5-Ar]]> -0.711 0.134 <![CDATA[Co-MoS2-1.0-Ar]]> -0.9 0.239 <![CDATA[Co-MoS2-2.0-Ar]]> -0.711 0.180
[0104] As can be seen from Table 3, when Co-MoS2-Ar, obtained by treating Co-MoS2 with Ar, is used as a catalyst for catalytic synthesis of ammonia, the ammonia concentration is greater than the concentration of Co-MoS2 catalytic synthesis of ammonia, which indicates that the performance of the catalyst for catalytic synthesis of ammonia has been improved after being treated with protective gas. When the molar ratio of cobalt acetate tetrahydrate to MoS2 is 1:1, the ammonia concentration is the highest and the catalytic synthesis of ammonia is the best. Figures 8 to 10 From the comparison between Figure (a) and Figure (b), it can be seen that at different molar ratios of cobalt acetate tetrahydrate and MoS2, the current density of the working electrode made of Co-MoS2 and Co-MoS2-Ar catalysts in N2O atmosphere is greater than that in Ar gas atmosphere, and the presence of product NH3 can be seen from Table 3, indicating that N2O can be reduced to ammonia by electrochemical means.
[0105] Example 10 Preparation and Application of Metal Manganese Modified MoS2
[0106] A method for preparing a transition metal modified MoS2 catalyst for electrochemical reduction of N2O to synthesize ammonia, wherein the steps are substantially the same as those of Example 1, except that the copper acetate tetrahydrate in step (2) is replaced by a Mn salt, and the molar ratios of the Mn salt to MoS2 are 0.5:1 and 2:1, respectively. Mn-MoS2-0.5 catalyst, Mn-MoS2-2.0 catalyst, Mn-MoS2-0.5-Ar and Mn-MoS2-2.0-Ar catalysts are prepared respectively, and the corresponding catalysts are used to electrochemically reduce N2O to synthesize ammonia.
[0107] After the reaction, 2 mL of electrolyte was taken and the appearance potential value and ammonia concentration of the product ammonia in Example 10 were tested by the indophenol blue detection method. The results are shown in Table 4. Under 10 mL / min Ar and N2O atmosphere, the linear sweep voltammetric curves (LSV curves) of the working electrodes made of Mn-MoS2 and Mn-MoS2-Ar catalysts at various molar ratios were measured. The test voltage range was -1.8 to -0.7 V (vs. ref). The results are shown in Table 4. Figures 11-12 shown.
[0108] Table 4 Synthetic ammonia concentration at different molar ratios of Mn salt and MoS2
[0109] Material Potential V (vs.ref) Ammonia concentration (ppm) <![CDATA[Mn-MoS2-0.5]]> -1.261 0.083 <![CDATA[Mn-MoS2-2.0]]> -1.261 0.062 <![CDATA[Mn-MoS2-0.5-Ar]]> -0.911 0.154 <![CDATA[Mn-MoS2-2.0-Ar]]> -1.011 0.188
[0110] It can be seen from Table 4 that when Mn-MoS2-Ar, obtained by treating Mn-MoS2 with Ar, is used as a catalyst to synthesize ammonia, the ammonia concentration is greater than that of Co-MoS2, which indicates that the performance of the catalyst in synthesizing ammonia has been improved after being treated with protective gas. Figures 11-12From the comparison between Figure (a) and Figure (b), it can be seen that the current density of the working electrode made of Mn-MoS2 and Mn-MoS2-Ar catalysts in N2O atmosphere is greater than that in Ar gas atmosphere, and the presence of product NH3 can be seen from Table 4, indicating that N2O can be reduced to ammonia by electrochemical means.
[0111] The catalyst prepared in Example 7 was subjected to characterization tests, including XRD test, XPS test, and Raman spectrum test. The test results are as follows: Fig.13 As shown. Fig.13 (a) The XRD spectrum of the Co-MoS2 catalyst shows that after the catalyst was treated with protective gas argon, the diffraction peak position of the 100 crystal plane shifted significantly to a higher angle, which is due to the reduction in the interlayer spacing. Fig.13 (b) Raman spectrum of Co-MoS2 catalyst shows that A 1g The peak intensity is greater than E 2g 1 Represents edge-end structure. 2g 1 and A 1g The peak spacing is about 26 cm. -1 , representing a multilayered sheet structure. The main peak position did not change after argon treatment, indicating that the structure of molybdenum disulfide did not change significantly after Ar treatment. 1g / E 2g 1 The smaller ratio after argon treatment confirms the stability of the multilayer structure of MoS2 and the possibility of reducing the number of layers, thereby exposing more active sites and improving the catalytic performance. Fig.13 (c) XPS spectrum of Co-MoS2 catalyst shows that after the catalyst is treated with protective gas argon, a blue shift occurs, indicating that its electronic structure has changed. The blue shift of Mo3d orbital indicates that metal p-type is doped in the MoS2 lattice.
[0112] Comparative Example 1
[0113] Comparative Example 1 provides a method for preparing a modified MoS2 catalyst for electrochemical reduction of N2O to synthesize ammonia, comprising the following steps:
[0114] (1) 1.2 g of ammonium molybdate tetrahydrate ((NH4)6Mo7O 24 ·4H2O) and 2.3g thiourea (CH4N2S) were dissolved in 40mL deionized water and stirred at room temperature for 30min; the stirred reaction solution was transferred to a 50mL polytetrafluoroethylene-lined stainless steel reactor and placed in an oven for hydrothermal synthesis at a reaction temperature of 160°C for 28h. The product obtained by hydrothermal synthesis was washed with deionized water and ethanol, then dried in an oven at 60°C for 4h, and ground to obtain MoS2 powder.
[0115] (2) The MoS2 powder prepared in step (1) is spread flat on a magnetic boat, and then placed in a tubular furnace, maintained at a temperature of 200°C for 2 h at a heating rate of 1°C / min under an Ar atmosphere, and then naturally cooled to room temperature to obtain a MoS2-Ar catalyst.
[0116] Comparative Example 1 also provides a method for electrochemically reducing N2O to synthesize ammonia, comprising the following steps:
[0117] 5 mg of MoS2 or MoS2-Ar catalyst was evenly dispersed and dropped on carbon paper to make a working electrode, and then assembled into a three-electrode system; in the three-electrode system, 40 mL of 0.1 mol / L Na2SO4 solution was used as the electrolyte, Ag / AgCl was used as the reference electrode, and the glassy carbon electrode was used as the counter electrode; the three-electrode system was connected to an electrochemical workstation and worked for 1 h in a 10 mL / min N2O atmosphere to synthesize ammonia, and the working voltage was -0.9 V (vs. ref).
[0118] After the reaction, 2 mL of electrolyte was taken and the appearance potential value and ammonia concentration of the product ammonia in Comparative Example 1 were tested by indophenol blue detection method. The results are shown in Table 5. Under 10 mL / min Ar and N2O atmosphere, the LSV curve with a voltage range of -1.8 to -0.7 V (vs. ref) was tested. The results are shown in Table 5. Fig.14 shown.
[0119] Table 5 Ammonia concentration of MoS2 and MoS2-Ar electrocatalytic N2O synthesis
[0120] Material Potential V (vs.ref) Ammonia concentration (ppm) <![CDATA[MoS2]]> -0.9 0.037 <![CDATA[MoS2-Ar]]> -0.9 0.082
[0121] It can be seen from Table 5 that when MoS2-Ar, obtained by treating MoS2 with Ar, is used as a catalyst to synthesize ammonia, the ammonia concentration is greater than the concentration of ammonia synthesized by MoS2. Fig.14 (a) It can be seen that the current density of MoS2 in Ar and N2O atmospheres is relatively close. Fig.14 (b) It can be seen that the current density of MoS2-Ar in N2O atmosphere is significantly greater than that in Ar gas atmosphere, and the production of product ammonia is detected, indicating that N2O can be reduced to ammonia by electrochemical means, and also indicating that the performance of the catalyst is improved after inert gas treatment. From the data comparison of the embodiment and comparative example 1, it can be seen that the doping of transition metal improves the performance of the catalyst in catalyzing the synthesis of ammonia.
Claims
1. A method for preparing a transition metal modified MoS2 catalyst, characterized in that: The following steps are involved: (1) dissolving molybdate and a sulfur-containing organic compound in water, stirring at room temperature for a period of time, and then performing a hydrothermal synthesis reaction at 160-200° C. for 20-28 hours, washing the hydrothermal synthesis product with water and ethanol, and then drying to obtain MoS2; (2) dissolving the transition metal salt and the MoS2 prepared in step (1) in an ethanol aqueous solution, stirring the reaction at room temperature for 4 to 6 hours, washing with water by centrifugation until neutral, and then drying to obtain a transition metal-doped MoS2 catalyst; (3) The transition metal-doped MoS2 catalyst prepared in step (2) is maintained at a temperature of 200 to 400°C at a heating rate of 1°C / min under a protective gas atmosphere for 2 to 4 hours, and then naturally cooled to room temperature to obtain a transition metal-modified MoS2 catalyst.
2. The preparation method according to claim 1, characterized in that: The molar ratio of the molybdate to the sulfur-containing organic compound in step (1) is 1:(30-50); The molybdate is (NH4)6Mo7O 24 , Na2MoO4; The sulfur-containing organic compound is at least one of C2H5NS and CH4N2S.
3. The preparation method according to claim 2, characterized in that: The molar ratio of the transition metal salt and MoS2 in step (2) is (0.5-2):1; the volume fraction of the ethanol aqueous solution is 25%.
4. The preparation method according to claim 3, characterized in that: The transition metal in step (2) is at least one of Cu, Ni, Mn and Co; and the transition metal salt is at least one of acetate, nitrate and sulfate of the corresponding metal.
5. The preparation method according to claim 4, characterized in that: The protective gas in step (3) is He, N2 or Ar.
6. A transition metal modified MoS2 catalyst prepared by the method described in any one of claims 1 to 5.
7. Use of the transition metal modified MoS2 catalyst according to claim 6 in electrochemical reduction of N2O to synthesize ammonia.
8. A method for synthesizing ammonia by electrochemical reduction of N2O, characterized in that: The method comprises the following steps: uniformly dispersing the catalyst prepared in claim 6 by ultrasonic treatment, dripping the catalyst onto carbon paper to prepare a working electrode, and assembling the working electrode into a three-electrode system; in the three-electrode system, using a 0.1 mol / L Na2SO4 solution as an electrolyte, Ag / AgCl as a reference electrode, and a glassy carbon electrode as a counter electrode; connecting the three-electrode system to an electrochemical workstation, reacting for 1 to 5 hours to synthesize ammonia in a voltage range of (-0.7) to (-1.3) V under an N2O atmosphere of 5 to 10 mL / min.
Citation Information
Patent Citations
Teflon double-doped tungsten disulfide nano-catalyst as well as preparation method and application thereof
CN117985761A
Preparation method of phosphomolybdic acid regulated metal organic framework Cu-MOF catalyst, product and application
CN118048646A
Cited By
Semiconductor phase MoS2 transition metal-based composite catalyst, preparation method thereof and application of composite catalyst in electro-catalysis of N2O to synthesize ammonia
CN122147410A
